Die Hochschulbibliothek der ZHAW als Begegnungs-, Beratungs- und Lernort für wissenschaftliches Schreiben und Arbeiten - Karras, Simone; Meyer Kälin, Margrit (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2024)
The university libraries increasingly see themselves as information and educational institutions, with the teaching of information literacy being considered as a central task of the libraries. Scientific writing and working, like information literacy, are key qualifications for successful studies. Academic writing competencies and information literacy are interrelated, and writing can be defined as part of information literacy in a broader sense. The library of the Zurich University of Applied Sciences (ZHAW) offers various events and formats for scientific writing and working, such as writing consultations, writing nights, and workshops for bachelor students, thereby imparting both information literacy- and writing-competencies. The library is a suitable teaching and learning environment for scientific writing and working, and thus assumes educational and training tasks across universities.